Protein phosphatase 2A propels follicular T helper cell development in lupus. Issue 136 (April 2023) - Jiang, Yu; Jin, Xuexiao; Chi, Zhexu; Bai, Yadan; Manthiram, Kalpana; Mudd, Pamela; Zhu, Kaixiang; Wang, Lie; Schwartzberg, Pamela L.; Han, Yongmei; Gao, Xiang; Lu, Linrong; et al.
Abstract: Follicular helper T (Tfh) cells are important for generating humoral immune responses by helping B cells form germinal centers (GCs) and the production of high-affinity antibodies. However, aberrant Tfh cell expansion also contributes to the generation of self-reactive autoantibodies and promotes autoantibody-mediated autoimmune diseases such as systemic lupus erythematosus (SLE). Protein phosphatase 2A catalytic subunit alpha isoform (PP2A Cα) expression levels are elevated in peripheral T cells of SLE patients and positively correlate with autoantibody titers and disease activity. Here, we demonstrate a critical role of PP2A in Tfh differentiation by using T cell restricted PP2A Cα deficient mice. We observed impaired Tfh differentiation and GC response in two different classical Tfh induction models. Mechanistic studies revealed that downregulation of protein translation of the Tfh lineage transcription factor BCL6 in PP2A deficient T cells. Importantly, we found that PP2A deficiency by either gene knockout or chemical inhibition alleviated lupus severity in mice. Lastly, we confirmed a positive correlation between PP2A Cα and BCL6 protein levels in human CD4 + T cells from patients with SLE. In summary, our study revealed a critical role of PP2A in regulating Tfh cells and suggests it is a potential therapeutic target for lupus. Graphical abstract: Image 1 Highlights: PP2A is requisite for the development of Tfh cells and normal GC function. PP2A deficiency lead to downregulation of BCL6 translation. PP2A T cell deficiency or PP2A inhibition significantly protected mice from lupus. Positive correlation of PP2A Ca and BCL6 protein levels in human lupus CD4 + T cells.